2000
DOI: 10.1097/00000539-200004000-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blinded Study of Remifentanil Versus Fentanyl for Tonsillectomy and Adenoidectomy Surgery in Pediatric Ambulatory Surgical Patients

Abstract: This is a study designed to examine the efficacy and safety of a short-acting opioid, remifentanil, when used in pediatric patients. The frequent incidence of postoperative pain observed in the postoperative recovery room suggests that better intraoperative prophylactic analgesic regimens for postoperative pain control are necessary to optimize remifentanil's use as an anesthetic for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 12 publications
0
34
0
1
Order By: Relevance
“…23 The use of remifentanil for tonsillectomy, rather than fentanyl, may be associated with higher postoperative pain scores and may therefore need better prophylactic analgesic regimens for control of postoperative pain. 24 Nevertheless, the use of morphine at the end of the surgery in our study may have decreased the requirement for postoperative rescue analgesics. Since there have been concerns regarding cardiovascular events associated with the use of rofecoxib and valdecoxib (the active metabolite of parecoxib), 25 the safety of parecoxib sodium in pediatric patients should be evaluated in larger clinical trials.…”
Section: Discussionmentioning
confidence: 72%
“…23 The use of remifentanil for tonsillectomy, rather than fentanyl, may be associated with higher postoperative pain scores and may therefore need better prophylactic analgesic regimens for control of postoperative pain. 24 Nevertheless, the use of morphine at the end of the surgery in our study may have decreased the requirement for postoperative rescue analgesics. Since there have been concerns regarding cardiovascular events associated with the use of rofecoxib and valdecoxib (the active metabolite of parecoxib), 25 the safety of parecoxib sodium in pediatric patients should be evaluated in larger clinical trials.…”
Section: Discussionmentioning
confidence: 72%
“…The effect of fentanyl on sevoflurane, which has been shown to be interchangeable with remifentanil in children, has been documented. 5,6 There exists a 1:1.5 potency ratio between fentanyl and remifentanil. 7 Zhang et al have shown that in children aged five to ten, an increase in fentanyl serum levels from 0.62 ± 0.13 µg·L -1 to 1.51 ± 0.18 µg·L -1 produces a decrease in sevoflurane MAC from 1.03 ± 0.07% to 0.64 ± 0.01%.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In children, remifentanil and fentanyl have been shown to be interchangeable clinically. 5,6 Remifentanil has been shown to have superior recovery characteristics and is effective at dosages much lower than those required for other commonly-used opioids such as fentanyl. 7 The effect of remifentanil in reducing the minimum alveolar concentration MAC-BAR of sevoflurane has been demonstrated in adults.…”
mentioning
confidence: 99%
“…Furthermore, the precise dosage of remifentanil that is associated with tolerance in this population has not been determined. Although the intraoperative infusion of 0.25 µg·kg −1 ·min −1 remifentanil is associated with high postoperative pain-discomfort scores in 2-to 12-yr-old children, 9 the intraoperative infusion of 0.8 µg·kg…”
Section: ·Minmentioning
confidence: 99%